A renewed framework for the essential public health functions in the Americas - Ernesto Bascolo; Natalia Houghton; Amalia del Riego; James Fitzgerald (Pan American Health Organization, 2020)
This report presents the results of a consensus decision making process conducted to elaborate a renewed conceptual framework of the essential public health functions for the Americas. The emerging framework consists of four pillars encompassing action-oriented components relating to the new scope and concerns of public health. The four pillars call for adopting a human rights approach to public health, addressing the social determinants of health, ensuring access to both individuals and population-based services, and expanding the stewardship role of health authorities through a collaborative implementation of public health functions. Public health functions were conceptualized as a set of capacities that are part of an integrated policy cycle the encompasses four stages: assessment, policy development, allocation of resources, and access. The framework provides a road map for evaluation and development by health authorities of integrated enabling public health policies through intersectoral collaboration. The application of the framework would require engaging countries working to improve public health through national assessments and systematic incorporation of these findings into quality improvement efforts and sectoral and intersectoral decision-making processes around policy and investments priorities promoted by governments. Work is ongoing in the definition of a list of public health functions that gives operational clarity to each dimension of this framework and guides performance evaluation.